A Catholic Positive Youth Development Model Based on the Context of the Catholic Church in Thailand - Patsriruang, Sarawin (Animo Repository, 2024)
In 2007, the Catholic Youth Council of Thailand was restructured into the Catholic Commission for Laity on Youth Desk to collaborate with all Catholic youth organizations in Thailand and expand the work of Catholic youth development. Despite the announcement of its 10 major youth development plans since 2015, there is still an opportunity to incorporate the widely adopted Positive Youth Development (PYD) approach into its projects and programs. Similarly, research on Catholic youth development reveals a gap in the concrete application of PYD. To address these practical and research gaps, this study aims to develop a PYD model suitable for Thai Catholic youth. A multimethod qualitative methodology was employed, consisting of a documentary analysis and expert interviews. The documentary analysis of 72 Papal Documents on youth provided a preliminary model of Catholic Positive Youth Development (CPYD). To ascertain and contextualize the preliminary model, expert interviews were conducted with five administrators and practitioners affiliated with the Catholic Commission for Laity’s Youth Desk, operating under the auspices of the Catholic Bishops’ Conference of Thailand. Based on the expert feedback, a revised CPYD model was obtained. The model is based on the original PYD model, aligns with the Papal teachings on youth, and responds to the context of Catholic youth development in Thailand.